DETERMINAN MIGRASI INTERNASIONAL TENAGA KERJA - Salsabilla, Adinda Thalia; Pratomo, Devanto Shasta (Journal of Development Economic and Social Studies, 2024)
Labor migration is a phenomenon that occurs in various regions, especially East Java Province as one of the provinces that has a high level of productivity. The movement of labor can be influenced by various factors. This study aims to analyze the determinants of international labor migration in East Java in 2015-2019. the type of data used in this study is secondary data. The research method used in this research is panel data regression. The results of the study show that the GRDP variable influences positively but not significantly, while poverty and unemployment variables influences negatively and react not significantly. Meanwhile, the district/city minimum wage variable influences negatively and significantly on the number of international labor migration in East Java.